2016
DOI: 10.1016/j.annepidem.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Potential selection bias associated with using geocoded birth records for epidemiologic research

Abstract: Purpose There is an increasing use of geocoded birth registry data in environmental epidemiology research. Ungeocoded records are routinely excluded. Methods We used classification and regression tree analysis (CART) and logistic regression to investigate potential selection bias associated with this exclusion among all singleton Florida births in 2009 (N=210,285). Results The rate of unsuccessful geocoding was 11.5% (n=24,171). This ranged between 0% to 100% across zip codes. Living in a rural zip code wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Indeed, others have previously found that excluding nongeocoded addresses can result in selection bias for epidemiological research. 23 This study found that living in a rural zip code was highly associated with geocoding status. Furthermore, even among addresses only in urban zip codes, geocoding status was associated with numerous factors, including maternal race, maternal smoking, and having nonprivate insurance.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, others have previously found that excluding nongeocoded addresses can result in selection bias for epidemiological research. 23 This study found that living in a rural zip code was highly associated with geocoding status. Furthermore, even among addresses only in urban zip codes, geocoding status was associated with numerous factors, including maternal race, maternal smoking, and having nonprivate insurance.…”
Section: Discussionmentioning
confidence: 73%
“…With increased accessibility to health delivery data by both public health and health care professionals, there has been an increase in the use of spatial analytics to monitor and understand the spread of disease and outbreak management responses 32 . For example, geographic information systems (GIS) allow communities to better utilize public health resources by targeting a community immunization response strategy to outbreak clusters 33 , although selection bias could be an issue, particularly for those from rural settings, certain ethnic or racial groups, and those with lower socio-economic status 34 . In addition, GIS surveillance can be assisted by social media.…”
Section: Resultsmentioning
confidence: 99%
“…Geocoding individual level records (by linking zip codes or census tracts, for example) is widely conducted in epidemiologic research to provide additional information, particularly when interested in environmental exposures (such as air pollution) or proxies for socioeconomic position (e.g., area-based deprivation). Ensuring accurate addresses when cleaning administrative data is crucial, as it has the potential to lead to mismatches, the consequences of which may be reduced sample sizes and increased selection and information biases [ 41 ].…”
Section: Cleaning and Codingmentioning
confidence: 99%